Keterbatasan Ekonomi Keluarga Petani dan Peran Motivasi Orang Tua terhadap Pendidikan Tinggi Anak Desa Alamendah - Zahara; Fani Kamelia Amanda; Muhammad Azka Ramadhan (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study examines how economic limitations of farming families affect children’s motivation to pursue higher education in Alam Endah Village. A descriptive qualitative method was applied using observation, interviews, and documentation. Findings reveal that while financial barriers exist, strong parental support and the role of institutions like Pesantren Al-Ittifaq encourage students to pursue their studies. Agro-tourism also contributes gradually to household income. However, inequality in access, limited educational literacy, and restrictive policies remain key obstacles. This research underlines the importance of collaboration between government, local institutions, and families to promote inclusive and equitable access to higher education in rural areas.